Blended Project Based Learning: Strategy for Improving Critical Thinking of Pre-Service Teachers in Science Education - Putri, Suci Utami; Hendawati, Yuyu (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this study was to analyze the effectiveness of blended project based learning to improve the critical thinking of pre-service teachers in science education. In this blended project based learning, students teacher must complete the multimedia project using various software and discuss the project and the concept through face-to-face and e-learning session. The content of multimedia project were developed based on science unit on the topics of Anatomy and Physiology of Human, Animal and Plant. The method of this research was mixed method with embedded design by involving 35 students teacher at Primary School Teacher Education in Indonesia University of Education, Purwakarta campus. The data were obtained using observation sheet and critical thinking test. The result showed that the students have a good activities in e-learning and face-to-face session and the critical thinking improved after the implementation of blended project based learning.